The Meaning Difference of Lexicon “Sakit” in Bimanese: A Semantic Perspective (e-Journal of Linguistics, 2020)
The current study attempts to describe the lexicon “sakit” in Bimaneseused by Mbojo ethnic group in daily communication and analyze themeaning difference from the semantic perspective. The research applieddescriptive qualitative method of analysis and the data were collectedby using fishbowl, recording, and note taking technique. Based on thedata analysis the findings reveal that thirteen lexicons “sakit“ are usedby Mbojo ethnic group in daily communication including supu [supu],hengge [hengge], sari’i [sari’i], rambo [rambo], mbalo [mbalo],mancoro [mancoro], kantero [kantero], duha [duha], pili [pili], ngelu[ngelu], ncara oi [ncara ᴐwi], mbowi [mb ᴐwi] and winte [winte].
Keywords: Lexicon “sakit”; Mbojo Ethnic group; Bimanese